2014
DOI: 10.1097/nmd.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Lysergic Acid Diethylamide-Assisted Psychotherapy for Anxiety Associated With Life-threatening Diseases

Abstract: A double-blind, randomized, active placebo-controlled pilot study was conducted to examine safety and efficacy of lysergic acid diethylamide (LSD)-assisted psychotherapy in 12 patients with anxiety associated with life-threatening diseases. Treatment included drug-free psychotherapy sessions supplemented by two LSD-assisted psychotherapy sessions 2 to 3 weeks apart. The participants received either 200 μg of LSD (n = 8) or 20 μg of LSD with an open-label crossover to 200 μg of LSD after the initial blinded tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
564
3
35

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 586 publications
(626 citation statements)
references
References 30 publications
24
564
3
35
Order By: Relevance
“…Finally, four separate studies have been published on the use of psychedelics in end-of-life anxiety associated with life threatening illness (Gasser et al, 2014;Griffiths et al, 2016;Grob et al, 2011;Ross et al, 2016). Charles Grob and colleagues, working in California, United States, gave 12 subjects (11 women) a moderate (0.2 mg/kg) dose of psilocybin and an active placebo (niacin 250 mg) several weeks apart with psychological support in a double-blind design in which subjects acted as their own control (Grob et al, 2011).…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, four separate studies have been published on the use of psychedelics in end-of-life anxiety associated with life threatening illness (Gasser et al, 2014;Griffiths et al, 2016;Grob et al, 2011;Ross et al, 2016). Charles Grob and colleagues, working in California, United States, gave 12 subjects (11 women) a moderate (0.2 mg/kg) dose of psilocybin and an active placebo (niacin 250 mg) several weeks apart with psychological support in a double-blind design in which subjects acted as their own control (Grob et al, 2011).…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
“…Peter Gasser and colleagues, working in Switzerland, gave LSD to 12 patients with anxiety associated with life threatening disease in a double-blind, randomised, active placebo controlled pilot trial (Gasser et al, 2014) with a 12 month qualitative follow up study also reported (Gasser et al, 2015). Drug free psychotherapy sessions were supplemented by two LSD assisted psychotherapy sessions given 2e3 weeks apart, in which participants were randomised to receive either 200 mcg or 20 mcg of LSD.…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
“…Modern experimental studies with hallucinogens in humans resumed in the 1990s with N-N-dimethyltryptamine (DMT, ayahuasca) (18)(19)(20)(21), ketamine (21)(22)(23), and psilocybin (24,25) but not with LSD. Both LSD and psilocybin have also been recently evaluated in pilot therapeutic studies as treatments for anxiety in patients with lifethreatening diseases (11,26). Because of the continued popularity of LSD as a recreational drug and renewed interest in its therapeutic use (11,27), we reexamined the acute response to LSD in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1950s to 1970s, LSD was initially used as an experimental tool ("psychotomimetic") to study psychotic-like states and model psychosis (4,5) and as an adjunct in "psycholytic psychotherapy." LSD has also been investigated for the treatment of alcoholism (6), addiction (7), cluster headache (8), and anxiety associated with terminal illness (9)(10)(11). Today, LSD is illicitly used for recreational (personal or spiritual) purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The dose makes the poison (Paracelsus). The rediscovery of beneficial effects of prohibited substances, starting with the prescription of Cannabis for defined indications, goes on for LSD (16) and Psylocibin (17). Others may follow.…”
Section: Summary Statementmentioning
confidence: 99%